Balls in Sequence Spaces - E. A. Timofeev (Моделирование и анализ информационных систем, 2015)
We introduce a new metric on a space of right-sided infinite sequences drawn from a finite alphabet. Emerging from a problem of entropy estimation of a discrete stationary ergodic process, the metric is important on its own part and exhibits some interesting properties. For example, the measure of a ball is discontinuous at every binary rational value of log r, where r is the radius.